Production of Nitric Oxide and Expression of Inducible Nitric Oxide Synthase in Ovarian Cystic Tumors - Rosekeila Simões Nomelini; Lívia Carolina de Abreu Ribeiro; Beatriz Martins Tavares-Murta; Sheila Jorge Adad; Eddie Fernando Candido Murta (Hindawi Limited, 2008)
Tumor sections from nonneoplastic (n=15), benign (n=28), and malignant ovarian tumors (n=20) were obtained from 63 women. Immunohistochemistry of the tumor sections demonstrated that inducible nitric oxide synthase (iNOS) expression was increased in ovarian cancer samples compared to nonneoplastic or benign tumor samples. Using the Griess method, nitric oxide (NO) metabolite levels were also found to be elevated in malignant tumor samples compared to benign tumor samples (P<.05). For stage I ovarian cancer, intracystic NO levels >80 μM were more frequent than NO levels <80 μM, and iNOS expression in well-differentiated carcinomas was greater than in moderately/poorly differentiated carcinomas (P<.05). These data suggest an important role for NO in ovarian carcinogenesis.